Post epic in the Max Frisch’s play “The Fire Raisers” - Василівська, Наталія Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article explores the features of Max Frish’s play “Тhe Fire Raisers”. The research has been conducted in the context of the covering of the processive aspect of the play as an example of a dramatic parable. The main points of the drama theorist and practice of the epic theater Bertolt Brecht and Max Frish as a representative of the dramatic art that arose after Brecht have been highlighted. The work analyzes the plot and meaning of the play, its philosophical value, thus demonstrating a new author’s vision of the principles of the epic Brechtian theater, the features of the drama-parable and “absurdism of the work” in terms of creating a special “model” of the play, a counterpoint to the В. Brecht “moralizing” motive, author’s provocation, which induces research, analysis, process-game, discussion. The article emphasizes the statement of the so-called “edification” in drama. The “effect of edification” is weakened due to the absurdization of the plot. The reinforcement of the absurdity of the situation is facilitated by the simultaneous display of two places of action with elements of absurdization. To express the latter, the parody of the plot, choir and assembling acquires a new semantic meaning. The article analyzes the presence of choirs commenting on the action, as well as the misbehavior of the character in order to arouse recipient’s mind (studying through the wrong, “asocial sample”, which needs correction). There has been considered a new, rational for the modern world gradual form of presentation, which awakens the reader’s mind, stimulating to the independent problem-solving.